Bench-to-bedside review: Lactate and the lung - Iscra, Fulvio (BioMed Central, 2002)
The ability of the isolated lung tissue to take up glucose and to release lactate is potentially similar to that of other body tissues. Nonetheless, when lung lactate exchange was assess in vivo in normal humans, no measurable lactate production could be detected. Lung lactate production may become clinically evident in disease states especially in the patients with acute lung injury or with acute respiratory distress syndrome. Potential mechanisms of lactate production by the injured lung may include not only the onset of anaerobic metabolism in hypoxic zones, but also direct cytokine effects on pulmonary cells and an accelerated glucose metabolism in both the parenchymal and the inflammatory cells infiltrating lung tissue. In addition, as skeletal muscle, lung tissue may show metabolic adaptations in response to systemic mediators and may contribute to the systemic metabolic response to severe illness even in the absence of direct tissue abnormalities.